2009
DOI: 10.1007/978-3-642-00596-1_18
|View full text |Cite
|
Sign up to set email alerts
|

On the Expressive Power of Restriction and Priorities in CCS with Replication

Abstract: Abstract. We study the expressive power of restriction and its interplay with replication. We do this by considering several syntactic variants of CCS ! (CCS with replication instead of recursion) which differ from each other in the use of restriction with respect to replication. We consider three syntactic variations of CCS ! which do not allow the use of an unbounded number of restrictions: CCS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 17 publications
4
22
0
Order By: Relevance
“…In particular, already in that paper it is observed that finite-net π -calculus processes originate finite P/T net systems (with inhibitor arcs). Similar observations on the interplay between parallel composition and restriction in recursive definitions, in different contexts, has been done also by others, e.g., [1]. Also important is the work of Meyer [23,24] in providing an unlabeled P/T net semantics for a fragment of the π -calculus; the main difference is that his semantics may offer a finite net representation also for some processes where restriction occurs inside recursion, but the price to pay is that the resulting net semantics may be incorrect from a causality point of view; for instance, in process (νc)(a.c.0 | b.c.0) | (ā.0 |b.0) the two synchronizations on a and b are causally dependent in his semantics.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…In particular, already in that paper it is observed that finite-net π -calculus processes originate finite P/T net systems (with inhibitor arcs). Similar observations on the interplay between parallel composition and restriction in recursive definitions, in different contexts, has been done also by others, e.g., [1]. Also important is the work of Meyer [23,24] in providing an unlabeled P/T net semantics for a fragment of the π -calculus; the main difference is that his semantics may offer a finite net representation also for some processes where restriction occurs inside recursion, but the price to pay is that the resulting net semantics may be incorrect from a causality point of view; for instance, in process (νc)(a.c.0 | b.c.0) | (ā.0 |b.0) the two synchronizations on a and b are causally dependent in his semantics.…”
Section: Resultssupporting
confidence: 84%
“…If TS 1 = TS 2 we say that R is a bisimulation on TS 1 . Two states q and q are bisimilar, q ∼ q , if there exists a bisimulation R such that (q, q ) ∈ R.…”
Section: Definition 1 a Labeled Transition System (Or Lts For Short) mentioning
confidence: 99%
See 3 more Smart Citations